2020
DOI: 10.1136/tsaco-2019-000406
|View full text |Cite
|
Sign up to set email alerts
|

Quantity of hemoperitoneum is associated with need for intervention in patients with stable blunt splenic injury

Abstract: Background In patients with hemodynamically stable blunt splenic injury (BSI), there is no consensus on whether quantity of hemoperitoneum (HP) is a predictor for intervention with splenic artery embolization (SAE) or failing nonoperative management (fNOM). We sought to analyze whether the quantity of HP was associated with need for intervention. Methods This retrospective cohort study included adult trauma patients with hemodynamically stable BSI admitted to six trauma centers between 2014 and 2016. Quantity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Overall, most patients were male (n = 58), were a median age of 26 (21-42) years old, most (n = 62) had no comorbidities, and 47 had been injured from a ski/snowboarding accident. Compared to admitted patients, significantly more females were transferred, (13/38 vs. 3/36, p = 0.007, Table 1), more had an abbreviated injury scale score (AIS) ≥ 3 (vs < 3) of the chest (31/38 vs. 7/35, p = 0.002) and had a higher injury severity score (16 (16-22) vs. 13 (9)(10)(11)(12)(13)(14)(15)(16), p = 0.008), in comparison to admitted patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, most patients were male (n = 58), were a median age of 26 (21-42) years old, most (n = 62) had no comorbidities, and 47 had been injured from a ski/snowboarding accident. Compared to admitted patients, significantly more females were transferred, (13/38 vs. 3/36, p = 0.007, Table 1), more had an abbreviated injury scale score (AIS) ≥ 3 (vs < 3) of the chest (31/38 vs. 7/35, p = 0.002) and had a higher injury severity score (16 (16-22) vs. 13 (9)(10)(11)(12)(13)(14)(15)(16), p = 0.008), in comparison to admitted patients.…”
Section: Resultsmentioning
confidence: 99%
“…The patient was initially stable in the interventional radiology suite but went straight to surgery after blood pressure plummeted. Other studies have indicated failure rates between 6-20%, and they mostly depend on age, ISS, splenic injury grade, and appropriateness of patient selection for NOM [15,[24][25][26][27][28][29]. This patient appears to have been appropriately triaged for SAE, because the patient was young (26 years old), had an ISS of 16, a splenic injury grade of 4, bordering on 5 upon admission, and had a moderate amount of hemoperitoneum, yet was initially stable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation